The Effect of Profitability and Investment Opportunity Set on Cash Dividend With Liquidity as Moderate Variables (Studied at Kompas 100 That Listed on JSX in 2008-2012 Period) - Farida Titik Kristanti; Fitrianingsih Fitrianingsih (Jurnal Manajemen dan Bisnis Indonesia, 2013)
Dividend policy is profits which will be distributed to shareholders as dividends and/or retained earnings that will be retained as financing for investments in the future. There are many factors that influenced dividen policy, such as, profitability, cash flow, price earning ratio, leverage, inventory turnover, etc. This study aimed to determine the influence of profitability and the investment opportunity set to the cash dividend policy with liquidity as a moderating variabel. The object of the research is emiten of Kompas 100 that listed on the Indonesian Stock Exchange in 2008-2012 period. The selection of the sample using Purposive sampling method that samples were obtained by 10 companies. Analytical methods used to test the hypothesis is Moderated Regression Analysis (MRA).Results of this study showed that the profitability and the investment opportunity set simultaneously significant effect on dividend policy with liquidity as a moderating variable. Regression coefficient indicates that 25.6% of the independent variables explain the dependent variable, the remaining 74.4% is explained by other variables. Partially profitability have no significant effect to the dividend policy with the positive direction, while investment opportunity set have significant influence to the cash dividen policy with a negative direction. The Liquidity able to moderate the relationship of profitability to the cash dividend policy with a negative direction, while the investment opportunit set can be moderated by liquidity to the dividend policy with a positive direction. Keyword : Dividend Policy, Liquidity, Profitability, and Set Investment Opportunities